The new EU countries and euro adoption - Hubert Gabrisch; Martina Kämpfe (Intereconomics, 2013)
In the new member states of the EU which have not yet adopted the euro, previous adoption strategies have come under scrutiny. The spillovers and contagion from the global financial crisis revealed a new threat to the countries' real convergence goal, namely considerable vulnerability to the transmission of financial instability to the real economy. This paper demonstrates the existence of extreme risks for real convergence and argues in favour of a new adoption strategy which does not announce a target date for the currency changeover and which allows for more flexible and countercyclical monetary, fiscal and wage policies.
Keywords: 330; EU-Erweiterung; Eurozone; EU-Beitrittskriterien; Wirtschaftliche Anpassung; Finanzkrise; EU-Staaten (Osteuropa)